2022
DOI: 10.7150/ijbs.71719
|View full text |Cite
|
Sign up to set email alerts
|

BMAL1 regulates Propionibacterium acnes-induced skin inflammation via REV-ERBα in mice

Abstract: Acne vulgaris is a common skin disease, affecting over 80% of adolescents. Inflammation is known to play a central role in acne development. Here, we aimed to investigate the role of the central clock gene Bmal1 in acne-associated inflammation in mice. To this end, mice were injected intradermally with Propionibacterium acnes ( P. acnes ) to induce acne-associated skin inflammation. We found that Bmal1 and its target ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Inflammatory arthritis [ 79 , 80 ], neuroinflammation [ 81 , 82 ] and metabolic inflammation [ 83 ] have been linked to the biological clock. In addition, inflammation of the retina [ 84 ], skin [ 85 ] and lungs [ 86 , 87 , 88 ] has been linked to circadian rhythms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammatory arthritis [ 79 , 80 ], neuroinflammation [ 81 , 82 ] and metabolic inflammation [ 83 ] have been linked to the biological clock. In addition, inflammation of the retina [ 84 ], skin [ 85 ] and lungs [ 86 , 87 , 88 ] has been linked to circadian rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the immune response via IL-1β was suppressed and inflammation was alleviated. BMAL1 regulatory effects on inflammation have also been linked to REV-ERBα [ 85 ]. In Bmal1 knockout mice with skin inflammation, p65 and NLRP3 levels were increased compared to their wild-type counterpart [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor BMAL1, an essential component of the molecular clock, regulates the upregulation of IL-6 in lipopolysaccharide-exposed microglia and plays a role in microglial inflammatory responses (45). The loss of BMAL1, or jetlag-sensitised mice, acts on the NF-kB/NLRP3 axis to promote inflammation, which exacerbates Propionibacterium acnes-induced skin inflammation (46). In addition, BMAL1 plays an important role in critical limb ischemia by activating IL-10, which transcriptionally suppresses inflammation and promotes angiogenesis via the transcriptional regulation of vascular endothelial growth factor expression (47).…”
Section: Discussionmentioning
confidence: 99%
“…SR8278 (a synthetic compound) is identified as an antagonist of REV-ERBα and widely used to probe the function of REV-ERBα (Kojetin et al, 2011;Pardee et al, 2011). Notably, we recently found that REV-ERBα restrains Propionibacterium acnes-induced skin inflammation through inhibiting the NF-κB/NLRP3 axis to protect against acne vulgaris (Li et al, 2022). However, it remains elusive whether and how REV-ERBα regulates skin aging.…”
Section: Introductionmentioning
confidence: 99%